Effects of alkalisation and volume fraction reinforcement of Bombyx mori silk fibre on the flexural strength of dental composite resins - Dyah Anindya Widyasrini; Siti Sunarintyas (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Composite resins are widely used in dentistry to restore dental caries. Recently, short fibre-reinforced composite (FRC) resins have been widely used for high-stress areas, especially in posterior teeth. Bombyx mori silk fibre is under research to reinforce dental composite resin as it has good mechanical properties. Purpose: This study aims to obtain the effects of alkalisation and silk fibre volume fraction on the flexural strength of FRC. Methods: Bombyx mori silk fibres were obtained from Perhutani, Pati, Indonesia. Samples were divided into two alkalisation groups (4% and 8%). Alkalisation of the silk fibres was conducted through the scouring process in NaOH, hydrolysis (30% H2SO4) and drying. Silk fibres were then reinforced in a resin matrix. The samples were subdivided based on the fibre volume fraction reinforcements, which were 0%, 5%, 10% and 15%. Each group of samples consisted of three specimens (n = 3). Flexural strength was measured using a universal testing machine. Data were analysed by two-way ANOVA (p < 0.05) and post-hoc least significant difference test (p < 0.05). Results: The results showed the flexural strength (MPa) means of the 4% alkalisation group were 169.31 ± 54.28 (0%), 76.08 ± 43.69 (5%), 107.86 ± 40.61 (10%) and 101.99 ± 10.61 (15%). The flexural strength (MPa) means of the 8% alkalisation group were 169.31 ± 54.28 (0%), 82.62 ± 22.41 (5%), 111.07 ± 32.89 (10%) and 153.23 ± 23.80 (15%). Statistical analysis by ANOVA indicated that the fibre volume fraction affected the flexural strength of composite resins. Conclusion: It can be concluded that the volume fraction of silk fibre increases the flexural strength of composite resins, although the strength is not as high as a composite resin without fibres. However, the alkalisation percentage did not affect the flexural strength of composite resins, and there was no interaction between alkalisation percentage and fibre volume fraction with the flexural strength of composite resins.